ACTIVE POWER LOSS REDUCTION AND IMPROVEMENT OF STATIC VOLTAGE STABILITY MARGIN INDEX BY WATERWAY ALGORITHM - Kanagasabai Lenin (SINERGI, 2018)
In this paper, the Waterway Algorithm (WA) is used for Active Power Loss Reduction and improvement of Static Voltage Stability Margin Index. The design of the Waterway Algorithm (WA) is imitated from nature and the whole waterway process which involves the flow of streams and rivers into the sea in the natural world. The proposed Waterway Algorithm (WA) algorithm has been tested on standard IEEE 30 bus test system and simulation results show clearly about the superior performance of the proposed algorithm in reducing the real power loss and upgrading the Static Voltage Stability Margin Index.